Lactobacillus plantarum TW1-1 Alleviates Diethylhexylphthalate-Induced Testicular Damage in Mice by Modulating Gut Microbiota and Decreasing Inflammation - Tian, Xiaozhu (Front Cell Infect Microbiol, 2019)
Diethylhexylphthalate (DEHP), acting as an endocrine disruptor, disturbed reproductive health. Here, we evaluated the effects of Lactobacillus plantarum TW1-1 (L. plantarum TW1-1) on DEHP-induced testicular damage in adult male mice. Results showed that oral supplementation of L. plantarum TW1-1 significantly increased the serum testosterone concentration, enhanced the semen quality, and attenuated gonad development defects in DEHP-exposed mice. L. plantarum TW1-1 also alleviated DEHP-induced oxidative stress and inflammatory responses by decreasing the mRNA expression and serum protein concentration of different inflammatory factors [tumor necrosis factor-α, interleukin (IL)-1β and IL-6]. Furthermore, L. plantarum TW1-1 significantly reduced DEHP-induced intestinal hyper-permeability and the increase in the serum lipopolysaccharide level. Gut microbiota diversity analysis revealed that L. plantarum TW1-1 shifted the DEHP-disrupted gut microbiota to that of the control mice. At phylum level, L. plantarum TW1-1 reversed DEHP-induced Bacteroidetes increase and Firmicutes decrease, and restored Deferribacteres in DEHP-exposed mice. Spearman's correlation analysis showed that Bacteroidetes, Deferribacteres, and Firmicutes were associated with DEHP-induced testicular damage. In addition, the ratio of Firmicutes to Bacteroidetes (Firm/Bac ratio) significantly decreased from 0.28 (control group) to 0.13 (DEHP-exposed group), which was restored by L. plantarum TW1-1 treatment. Correlation analysis showed that the Firm/Bac ratio was negatively correlated with testicular damage and inflammation. These findings suggest that L. plantarum TW1-1 prevents DEHP-induced testicular damage via modulating gut microbiota and decreasing inflammation.